Development of Android-Based Millealab Virtual Reality Media in Natural Science Learning - Zulherman Zulherman*; Gufron Amirulloh; Ariyadi Purnomo; Galih Baskoro Aji; Supriansyah Supriansyah (Jurnal Pendidikan Sains Indonesia, 2021)
Basically, media is something that cannot be separated from the learning component. The use of unattractive and varied media can make students bored and bored when the learning process takes place. This research was conducted with the aim of developing or producing a learning media product based on the use of virtual reality technology. The method used in this research is the research and development (RD) method. This media development focuses on learning Natural Sciences for grade V Elementary Schools. The initial stage of this research is by validating media experts and material experts. Then test the feasibility of media products to the teacher before testing the product to students. The results of the validation by media experts and material experts obtained criteria strongly agree with the results of validation by media experts by 85% and material experts by 92%. Then the media feasibility test conducted by the teacher obtained 89% results with the criteria strongly agree. The feasibility of media products for use by students was carried out through product trials at SDS Muhammadiyah 9 Jakarta with a total of 21 students. The results obtained show a percentage of 86% with very agree criteria.